Nickel-based phosphide for oxygen evolution reaction in alkaline water electrolysis using sodium hypophosphite replacement and pyrolysis and preparation method thereof
By using sodium hypophosphite replacement and pyrolysis in the preparation of nickel-based phosphide catalysts, the amount of phosphorus precursor is reduced, and a porous structure is formed. This solves the problem that phosphide catalysts in the prior art are not suitable for large-scale production, and achieves high oxygen generation performance and economy.
Patent Information
- Application Number
- CN202480052239.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-09
- Filing Date
- 2024-08-07
- Publication Date
- 2026-03-17
AI Technical Summary
Existing technologies for preparing non-precious metal phosphide catalysts for alkaline water electrolysis anodes suffer from problems such as excessive use of phosphorus precursors and unsuitability for large-scale production. In particular, chemical vapor deposition results in poor contact, and electroplating makes it difficult to manufacture powdered catalysts.
By replacing sodium in sodium hypophosphite with nickel and a second metal, a precursor in the form of nickel hypophosphite or a second metal hypophosphite is prepared. The amount of phosphorus input is reduced during pyrolysis, and sodium chloride is recrystallized from ethanol to form a porous structure, thereby increasing the surface area of the catalyst.
It achieves high phosphide yield and economic efficiency for large-scale production, while improving the oxygen generation and OER performance of the catalyst, exhibiting excellent catalytic characteristics and reducing the use of precious metals.
Smart Images

Figure CN121693391A_ABST
Abstract
Description
Cross-references to related applications
[0001] This application claims the benefit of Korean Patent Application No. 10-2023-0104171, filed with the Korean Intellectual Property Office on August 9, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] This disclosure relates to nickel-based phosphide catalysts using sodium hypophosphite (NaH2PO2) for displacement and pyrolysis, and methods for their preparation. More specifically, it relates to a highly active non-precious metal phosphide catalyst for oxygen evolution reaction in alkaline water electrolysis anodes, and methods for its preparation. This catalyst reduces the amount of phosphorus precursors used, does not use precious metals, and can be produced on a large scale. Background Technology
[0003] Hydrogen energy, with its abundant resources and lack of harmful emissions, is gaining attention as an environmentally friendly alternative to fossil fuels. Alkaline water electrolysis, as one method of hydrogen production, is less expensive than polymer electrolyte membrane and solid oxide water electrolysis, making it suitable for large-scale production. The oxygen evolution electrode has the greatest impact on the reaction rate in alkaline water electrolysis. The oxygen evolution reaction (OER) in alkaline electrolytes proceeds through four OH groups... - O2 is generated through a four-electron reaction, thus exhibiting a slower reaction rate compared to the hydrogen evolution reaction. Due to the complex reaction mechanism and slow reaction rate, a high overpotential is generated at the OER electrode, which is the main reason for the low efficiency of alkaline electrolysis. Therefore, using a catalyst with low overpotential for the OER reaction in alkaline water electrolysis cells is crucial for improving cell and stack efficiency.
[0004] Electrochemical catalysts for the oxidation-reaction (OER) of alkaline water electrolysis are known, with noble metal oxide catalysts such as IrO2 and RuO2 exhibiting excellent OER performance. However, since Ir and Ru are expensive and limiting noble metals, it is necessary to develop non-noble metal catalysts to replace them. Unlike acidic environments, alkaline water electrolysis can use relatively inexpensive transition metals such as Ni, Fe, and Co as catalyst materials. Among these, Ni is known to have excellent electrochemical reaction rates and corrosion resistance in alkaline solutions and is easily alloyed with other metals; therefore, Ni-based alloy catalysts are under active investigation.
[0005] Research on reducing the Tafel slope by doping Ni with nonmetallic elements such as O, P, N, S, and Se as a method for preparing Ni-based OER catalysts is actively underway. It has been reported that Ni₂P, NiCo₂O₃, and Ni₃Se₂ exhibit Tafel slopes similar to RuO₂ and IrO₂ in the oxygen evolution reaction. Among nonmetallic elements, nickel phosphide (NiP) catalysts using P have a core (phosphide)-shell (oxide) structure, in which the phosphide on the catalyst surface is eluted during OER measurements. This core-shell structure is known to possess excellent catalytic activity and durability because it improves OER performance through the oxide in the shell, and the phosphide in the core compensates for insufficient conductivity in the shell.
[0006] To further improve the performance of this NiP catalyst, methods for preparing or doping dissimilar alloys by introducing a second metal are being actively investigated. Many papers report that NiCoP, NiFeP, and NiFeCoP catalysts produced by alloying two or more metals exhibit higher OER performance than single-metal phosphides of NiP, CoP, and FeP. It has also been reported that when Fe is doped into NiCoP, Fe optimizes the electronic structure and improves OER performance.
[0007] However, the most widely used method for preparing such metal phosphides is chemical vapor deposition (CVD). CVD uses sodium hypophosphite (NaH₂PO₂) as a phosphorus precursor to generate phosphine (PH₃) at high temperatures, and is the most widely used method in phosphide preparation. However, the CVD method involves heat-treating NaH₂PO₂ while separating it from the metal precursor, leading to poor contact between the metal and PH₃. Therefore, metal phosphides are prepared by adding the metal precursor and NaH₂PO₂ at a mass ratio of 1:5 to 20. This CVD method is not only uneconomical due to the use of excessive phosphorus precursor, but also results in low contact between the PH₃ generated from the phosphorus precursor and the metal precursor, which is detrimental to large-scale production. Another method for preparing metal phosphides is electroplating, which requires a substrate such as foamed Ni as the substrate for electroplating. This electroplating method is a simple catalyst manufacturing method, but it is difficult to manufacture powdered catalysts, and therefore it is not suitable for alkaline anion exchange membrane water electrolysis (AEMWE).
[0008] To address this issue, there is a need to develop a highly active non-precious metal phosphide catalyst in powder form for alkaline water electrolysis anodes that can be produced on a large industrial scale while reducing the amount of phosphorus precursors required. Summary of the Invention
[0009] Technical issues The purpose of this disclosure is to provide a method for preparing a highly active non-precious metal phosphide catalyst for the oxygen evolution reaction in an alkaline water electrolysis anode, which can achieve large-scale production while reducing the amount of phosphorus precursors used.
[0010] Specifically, according to this disclosure, sodium in sodium hypophosphite, which serves as a phosphorus precursor, is replaced with nickel and a second metal to prepare a precursor in the form of nickel hypophosphite or a second metal hypophosphite. The nickel hypophosphite and the second metal hypophosphite are then pyrolyzed to prepare nickel-based phosphides. This reduces the amount of phosphorus input to twice that of the metal, compared to conventional methods that set the molar ratio of phosphorus to metal to 5 to 20 times the metal to generate hydrophosphides (PH3) and prepare phosphides. Furthermore, the pyrolysis of the nickel hypophosphite and the second metal hypophosphite themselves to obtain nickel-based phosphides provides a preparation method that allows for high phosphide yields and large-scale production, and is more economically and technologically advantageous than existing methods.
[0011] More specifically, according to this disclosure, in the preparation of nickel hypophosphite and the second metal hypophosphite precursor, sodium in the sodium hypophosphite bonds with chlorine contained in the metal salt, thus sodium chloride can be easily removed during water washing and serves as a filler to increase the surface area of the final nickel-based phosphide. Furthermore, the second metal performs a doping function to adjust the electronic structure of nickel, thereby improving the oxygen generation performance of the nickel phosphide, and any remaining second metal not doped into the nickel phosphide during heat treatment can be easily removed during washing, thus performing a second filler function. Therefore, this disclosure aims to provide a method for preparing a porous nickel phosphide catalyst doped with a small amount of the second metal while exhibiting excellent oxygen generation performance.
[0012] Technical solution According to one embodiment of this disclosure, a method for preparing a nickel-based phosphide represented by the following chemical formula 1 is provided, comprising the following steps: dissolving nickel chloride as a first metal, a second metal (M) chloride, and sodium hypophosphite (NaH2PO2) in water (step 1); evaporating the solvent to obtain a mixture of a nickel phosphide precursor and a second metal phosphide precursor (step 2); pyrolyzing the nickel phosphide precursor and the second metal phosphide precursor mixture to obtain a composition containing a nickel-based phosphide (step 3); and washing the composition with water to obtain a nickel-based phosphide (step 4). [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
[0013] According to another embodiment of this disclosure, a nickel-based phosphide is provided, which is represented by the following chemical formula 1 and has a concentration of 10m. 2 / g or larger BET surface area: [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
[0014] According to another embodiment of this disclosure, an alkaline water electrolysis system is provided, which includes a nickel-based phosphide as an anode catalyst.
[0015] Beneficial effects According to the method for preparing the nickel-based phosphide catalyst disclosed herein, in order to use M with an oxidation state of +2 2+ Replaces Na with an oxidation state of +1 in sodium hypophosphite (NaH2PO2) + By adding NaH2PO2 at a molar ratio of 2 to that of metal chloride (MCl2), a precursor M(H2PO2)2 with metal-phosphorus bonding is generated. This precursor is then pyrolyzed, leaving behind metal phosphide ash and generating a catalyst, thus allowing for high yield and large-scale production.
[0016] Furthermore, according to the preparation method disclosed herein, during the washing process, most of the second metal is removed from the nickel-based phosphide ash, leaving only a small amount of residue. This not only provides the nickel phosphide with a second metal doping effect, but also acts as a filler to form a porous surface at the location where the second metal dissolves.
[0017] Furthermore, according to the preparation method of this disclosure, ethanol is added during the solution stage of dissolving sodium hypophosphite (NaH2PO2) and metal chloride (MCl2) to induce recrystallization of sodium chloride (NaCl), which has low solubility in ethanol. The recrystallized sodium chloride can be uniformly mixed with the M(H2PO2)2 precursor. This can dissolve during the washing process and act as a filler, thereby allowing the production and supply of highly active nickel second metal phosphide catalysts with a large specific surface area.
[0018] Furthermore, although the nickel second metal phosphide catalyst for the oxygen evolution reaction (OER) in the alkaline water electrolysis anode of this disclosure uses a non-precious metal alloy, it has higher OER performance than iridium, which is a precious metal catalyst, and therefore has excellent catalytic characteristics and higher phosphide yield. Unlike the CVD method, it does not require contact between nickel and PH3, thus it is advantageous in terms of economy and process. Attached Figure Description
[0019] Figure 1 This is a schematic diagram illustrating the preparation method of nickel-iron phosphide catalyst.
[0020] Figure 2 The images are X-ray diffraction (XRD) patterns of the catalysts prepared in Experimental Example 1 by varying the heat treatment temperature to 500°C, 400°C, 300°C, and 200°C.
[0021] Figure 3 This is a linear sweep voltammetry (LSV) plot evaluating the oxygen evolution reaction (OER) of the nickel-iron phosphide catalyst prepared according to the heat treatment temperature in Experimental Example 1 when applied to a rotating disk electrode (RDE).
[0022] Figure 4 These are the XRD patterns of the catalyst before and after washing in Experiment Example 2.
[0023] Figure 5 These are scanning electron microscope (SEM) images of the catalyst before washing (a) and after washing (b) in Experiment Example 2.
[0024] Figure 6 This is the X-ray photoelectron spectroscopy (XPS) spectrum of Experiment Example 3.
[0025] Figure 7 This is the LSV plot used to evaluate OER in Experiment Example 3.
[0026] Figure 8 This is a schematic diagram illustrating the differences in the final products prepared according to the methods of Examples 1 and 2.
[0027] Figure 9 These are SEM images of Examples 1 and 2 of Experiment 4.
[0028] Figure 10 This is the LSV plot used to evaluate OER in Experiment Example 4.
[0029] Figure 11 This is the LSV plot used to evaluate OER in Experiment Example 5.
[0030] Figure 12 This is the electrochemical impedance spectroscopy (EIS) spectrum evaluated in Experimental Example 5.
[0031] Figure 13 This is the LSV plot used to evaluate OER in Experiment Example 6. Detailed Implementation
[0032] The terms “first,” “second,” etc., are used in this document to explain various elements, and these terms are used only to distinguish one constituent element from other constituent elements.
[0033] The technical terms used herein are provided to describe exemplary embodiments but are not intended to limit this disclosure. Unless the context clearly indicates otherwise, the singular forms include the plural forms. It should be understood that the terms “comprising,” “including,” “having,” etc., are used herein to specify the presence of the stated feature, integer, step, component, or combination thereof, but do not exclude the presence or addition of one or more other features, integers, steps, components, or combinations thereof.
[0034] Furthermore, when it is stated that each layer or element is formed "on" or "above" each layer or element, it means that each layer or element is formed directly above each layer or element, or that other layers or elements may be formed separately between layers or on an object or substrate.
[0035] While various modifications and forms may be made to this disclosure, specific embodiments will be described and explained in detail below. However, it should be understood that these are not intended to limit this disclosure to the particular disclosure, and that this disclosure includes all modifications, equivalents, or substitutions thereof without departing from the spirit and scope of this disclosure.
[0036] The preparation method of a highly active non-precious metal phosphide catalyst for an alkaline water electrolysis anode according to embodiments of the present disclosure will now be described in detail.
[0037] The purpose of this disclosure is to provide a method for preparing a highly active non-precious metal phosphide catalyst for alkaline water electrolysis anodes, which can achieve large-scale production while reducing the amount of phosphorus precursors used.
[0038] The preparation method according to one embodiment of this disclosure may include the following steps: Nickel chloride (as the first metal), chloride of the second metal (M), and sodium hypophosphite (NaH2PO2) are dissolved in water (step 1); Evaporate the solvent to obtain a mixture of nickel phosphide precursor and second metal phosphide precursor (step 2); Pyrolysis of the nickel phosphide precursor and the mixture of the second metal phosphide precursor yields a composition containing a nickel-based phosphide (step 3); and Wash the composition with water to obtain a nickel-based phosphide (step 4): The nickel-based phosphide obtained above is represented by the following chemical formula 1.
[0039] [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
[0040] Specifically, Figure 1 This is a schematic diagram illustrating a method for preparing phosphides using sodium hypophosphite (NaH2PO2) by displacement and pyrolysis according to the present disclosure.
[0041] In order to use M with an oxidation state of +2 2+ Replace Na with +1 oxidation state in sodium hypophosphite (NaH2PO2) + NaH2PO2 was added at a molar ratio of at least twice that of the metal chloride (MCl2) to prepare the precursor M(H2PO2)2, which was then pyrolyzed to prepare the metal phosphide.
[0042] Specifically, the metal salt and hypophosphite are dissolved in deionized water at a molar ratio of 1:2 (step 1). The solution is evaporated to remove only water, thereby obtaining a mixture of M(H₂PO₂)₂ (step 2). The mixture of the nickel phosphide precursor and the second metal phosphide precursor is pyrolyzed in an inert gas atmosphere to obtain a composition containing the metal phosphide (step 3). The obtained composition is washed with water, especially deionized water, to obtain the metal phosphide (step 4).
[0043] Nickel-based phosphides can be represented by the following chemical formula 1.
[0044] [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
[0045] Specifically, x can be 0.01 or greater, or 0.03 or greater, or 0.06 or greater, or 0.07 or greater up to 0.15 or less, or 0.12 or less, or 0.10 or less, or 0.80 or less.
[0046] Specifically, y can be 0.5 or greater, or 0.7 or greater, or 0.9 or greater, or 0.99 or greater up to 1.2 or less, or 1.1 or less, or 1.06 or less.
[0047] Preferably, M can be Fe.
[0048] In the preparation of the nickel-based catalyst, only a small amount of the second metal added is doped into the nickel-based phosphide. During the washing process, the remaining undoped second metal is removed using water (deionized water). Since the number of pores formed in the nickel-based catalyst is as large as the amount of undoped second metal removed, the second metal can function as a filler during the preparation process. Therefore, using the second metal can increase the surface area of the nickel-based phosphide catalyst and improve catalytic efficiency. That is, the second metal is only partially doped into the catalyst, and the remainder is washed away, so that the content of the second metal in the prepared catalyst meets the range x of chemical formula 1.
[0049] Step 1 is the process of dissolving nickel chloride (as the first metal), chloride of the second metal (M), and sodium hypophosphite (NaH2PO2) in water.
[0050] The second metal of the second metal salt other than the nickel salt can be at least one selected from the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr, and V. Furthermore, the second metal salt can be in the form of a chloride, specifically MCl2. Preferably, the second metal can be iron (Fe), and the second metal salt can be FeCl2.
[0051] The water used as a solvent can be deionized water.
[0052] In step 1, the mixing ratio of the nickel salt and the second metal salt with sodium hypophosphite is such that for every 100 moles of nickel chloride and the second metal chloride, 200 to 300 moles of sodium hypophosphite are mixed. Preferably, for every 100 moles of nickel chloride and the second metal chloride, sodium hypophosphite may be contained in 200 moles.
[0053] Considering that nickel has an oxidation state of +2 or that the second metal has an oxidation state of +1 for sodium hypophosphite (NaH2PO2),... + The substitution of the nickel salt and the second metal salt, as well as the final oxygen production efficiency and specific surface area of the catalyst, preferably involve mixing the total amount of nickel salt and the second metal salt with sodium hypophosphite within the above molar ratio range.
[0054] In step 1 above, the mixing ratio of nickel chloride and the second metal chloride can be 30 to 300 moles of the second metal chloride for every 100 moles of nickel chloride.
[0055] Preferably, the mixing ratio can be 50 to 200 moles of the second metal chloride for every 100 moles of nickel chloride, more preferably, 100 moles of the second metal chloride for every 100 moles of nickel chloride.
[0056] When the molar ratio of nickel salt to the second metal salt meets the above range, Ni2P, which serves as the catalyst framework, is effectively formed, and the catalyst surface area is greatly increased, thus the catalyst can achieve excellent oxygen production efficiency.
[0057] Following step 1, the method may further include the step of recrystallizing sodium chloride (NaCl) from a solution of nickel chloride, a second metal (M) chloride, and sodium hypophosphite dissolved in water.
[0058] Specifically, the recrystallization step of sodium chloride may include recrystallizing sodium chloride by adding a solvent in which sodium chloride has low solubility to nickel chloride, a second metal (M) chloride, and sodium hypophosphite dissolved in water.
[0059] Preferably, the solvent in which sodium chloride has low solubility can be ethanol.
[0060] If a solvent with low solubility for sodium chloride is added to a solution of nickel chloride, a second metal (M) chloride, and sodium hypophosphite, the sodium chloride recrystallizes. In this case, Ni₂P is effectively formed as a catalyst framework, and the sodium chloride is uniformly distributed among the precursors. This sodium chloride is then removed during washing, forming pores in the nickel-based phosphide catalyst, thus exhibiting a filling effect during preparation. Therefore, when ethanol is used, sodium chloride recrystallizes readily, maximizing the filling effect and significantly increasing the catalyst's surface area due to pore formation, which can further improve the catalyst's oxygen production efficiency.
[0061] Step 2 is the step of evaporating the solvent to obtain a mixture of nickel phosphide precursor and second metal phosphide precursor. If a further step of recrystallizing sodium chloride is performed, water and solvent can be evaporated to obtain a mixture of nickel phosphide precursor and second metal phosphide precursor in which sodium chloride crystals are dispersed.
[0062] In step 2, the nickel phosphide precursor can be nickel hypophosphite (Ni(H2PO2)2-), and the second metal phosphide precursor can be a second metal hypophosphite (M(H2PO2)2).
[0063] The solvent can be water, and the water can be deionized water.
[0064] Additionally, the solvent may include solvents added to recrystallize sodium chloride. The solvent added to recrystallize sodium chloride may be a solvent in which sodium chloride has low solubility, preferably ethanol.
[0065] If the solvent is evaporated in step 2, a mixture of nickel phosphide precursor and second metal phosphide precursor in powder form can be obtained. If the step of recrystallizing sodium chloride is further carried out, a mixture of nickel phosphide precursor and second metal phosphide precursor in powder form with dispersed sodium chloride crystals can be obtained.
[0066] Step 3 is a step of pyrolyzing a mixture of nickel phosphide precursor and second metal phosphide precursor to obtain a composition containing nickel-based phosphides.
[0067] The pyrolysis temperature can be from 250°C to 500°C. Preferably, the pyrolysis temperature can be from 250°C to 400°C or from 250°C to 300°C.
[0068] By ensuring the heat treatment temperature falls within the aforementioned range, the increase in impurities that combine with the second metal (especially iron (Fe)) and oxygen (O) is relatively small, and the BET surface area is significantly increased, thus enabling the catalyst to achieve excellent oxygen generation efficiency.
[0069] Alternatively, the pyrolysis in step 3 can also be a heat treatment process carried out in an inert gas atmosphere for about 90 minutes. Preferably, the inert gas can be argon.
[0070] Step 4 may be a step of washing the composition obtained in step 3 with water to obtain a nickel-based phosphide.
[0071] Compositions containing nickel-based phosphides may include nickel-based phosphides, pyrolysis byproducts, and a second metal, which are obtained by pyrolysis of nickel phosphide precursors and second metal phosphide precursors.
[0072] Pyrolysis byproducts may include sodium chloride (NaCl). Sodium chloride can be produced by the reaction between sodium in sodium hypophosphite and chlorine in nickel chloride or a second metal chloride.
[0073] Furthermore, during the washing process in step 4, any residual second metal not doped in the nickel-based phosphide can be removed. For example, iron can be removed in a chloride state.
[0074] The pyrolysis byproducts sodium chloride (NaCl) and a second metal can exist as fillers in the catalyst until the pyrolysis process, leaving pores in the catalyst and being washed away during the washing step. Thus, the catalyst can be made porous through the washing process. Furthermore, the second metal can be partially doped into the catalyst and dissolved in water as ferric chloride (e.g., FeCl2) and removed, thereby imparting porous properties to the catalyst.
[0075] The advantage of nickel-based phosphide catalysts that partially dope a second metal is that, compared with conventional phosphide catalysts containing only nickel, the second metal modifies the electronic structure of nickel in a direction that further enhances electrophilicity, so that more OH-, which is used as a material for water electrolysis, is adsorbed onto the electrode, thereby improving OER performance.
[0076] The water used in the washing process can be deionized water.
[0077] One embodiment of this disclosure can provide a nickel-based phosphide catalyst prepared by the above preparation method.
[0078] Specifically, nickel-based phosphides can be represented by the following chemical formula 1. [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
[0079] Specifically, x can be 0.01 or greater, or 0.03 or greater, or 0.06 or greater, or 0.07 or greater up to 0.15 or less, or 0.12 or less, or 0.10 or less, or 0.80 or less.
[0080] Specifically, y can be 0.5 or greater, or 0.7 or greater, or 0.9 or greater, or 0.99 or greater up to 1.2 or less, or 1.1 or less, or 1.06 or less.
[0081] Preferably, M can be Fe.
[0082] Nickel-based phosphides can have 10m 2 / g or larger BET surface area.
[0083] Preferably, the surface area of BET can be 10m². 2 / g or larger, 11m 2 / g or greater, 20m 2 / g or greater, 30m 2 / g or greater, or 32m 2 / g or greater, or 35m 2 / g or greater, or 37m 2 / g or greater, or 40m 2 / g or greater, or 42m 2 / g or greater, or 45m 2 / g or up to 50m 2 / g or less, or 48m 2 / g or less, or 46m 2 / g or less.
[0084] When prepared according to the preparation method of this disclosure, the nickel-based phosphide has a porous structure, which results in a large specific surface area and excellent oxygen generation efficiency when used as an oxygen generation catalyst.
[0085] According to another embodiment of this disclosure, an anode catalyst comprising nickel-based phosphides for alkaline water electrolysis can be provided.
[0086] Furthermore, according to yet another embodiment of this disclosure, an alkaline water electrolysis system comprising an anode catalyst can be provided.
[0087] Preferred embodiments are provided below to better understand this disclosure. However, the following embodiments are for illustrative purposes only and are not intended to limit the scope of this disclosure.
[0088] Example 1: Preparation of NiFeP catalyst using NaH2PO2 displacement and pyrolysis To prepare nickel-iron phosphide, nickel(II) chloride hexahydrate (NiCl₂·6H₂O) and iron(II) chloride tetrahydrate (FeCl₂·4H₂O) were used in a molar ratio of 1:1. Additionally, 200 molar parts of sodium hypophosphite (NaH₂PO₂) were added for every 100 molar parts of nickel(II) chloride hexahydrate and iron(II) chloride tetrahydrate, dissolving the nickel(II) chloride hexahydrate, iron(II) chloride tetrahydrate, and sodium hypophosphite in deionized water. At this point, 4.75 g of NiCl₂·6H₂O, 4.06 g of FeCl₂·4H₂O, and 8.56 g of sodium hypophosphite were used, along with 40 mL of deionized water.
[0089] Ethanol is added to a solution containing dissolved chloride and sodium hypophosphite to make Na... + and Cl - It recrystallizes to sodium chloride (NaCl).
[0090] Water and ethanol were removed from the sodium chloride recrystallization solution using an evaporator, thereby obtaining a powder of Ni(H2PO2)2 and Fe(H2PO2)2 precursor mixture dispersed with sodium chloride crystals.
[0091] The recovered mixture of Ni(H2PO2)2 and Fe(H2PO2)2 precursors containing dispersed sodium chloride crystals was spread on an alumina boat for heat treatment and placed in a furnace for heat treatment at 300°C for 90 minutes under a 100% argon atmosphere.
[0092] After heat treatment, the mixture was washed with deionized water and filtered three times, dried in an oven at 80°C for 3 hours, and then the nickel-iron phosphate was recovered.
[0093] Example 2: Preparation of NiFeP catalyst without sodium chloride recrystallization To prepare nickel-iron phosphide, nickel(II) chloride hexahydrate (NiCl₂·6H₂O) and iron(II) chloride tetrahydrate (FeCl₂·4H₂O) were used in a molar ratio of 1:1. Additionally, 200 molar parts of sodium hypophosphite (NaH₂PO₂) were added for every 100 molar parts of nickel(II) chloride hexahydrate and iron(II) chloride tetrahydrate, dissolving the nickel(II) chloride hexahydrate, iron(II) chloride tetrahydrate, and sodium hypophosphite in deionized water. At this point, 4.75 g of NiCl₂·6H₂O, 4.06 g of FeCl₂·4H₂O, and 8.56 g of sodium hypophosphite were used, along with 40 mL of deionized water.
[0094] Water is removed from the solution using an evaporator to obtain a powder mixture of Ni(H2PO2)2 and Fe(H2PO2)2 precursors.
[0095] The recovered Ni(H2PO2)2 and Fe(H2PO2)2 precursor mixture was spread on an alumina boat for heat treatment, placed in a furnace, and heat-treated at 300°C for 90 minutes under a 100% argon atmosphere.
[0096] After heat treatment, the mixture was washed with deionized water and filtered three times, dried in an oven at 80°C for 3 hours, and then the nickel-iron phosphate was recovered.
[0097] Comparative Example 1: Preparation of Nickel Phosphide NiP Catalysts via NaH2PO2 Replacement and Pyrolysis To prepare the nickel phosphide, nickel(II) hexahydrate (NiCl2·6H2O) was used as the metal chloride. Furthermore, 9.5 g of NiCl2·6H2O and 8.56 g of NaH2PO2 were added to 40 mL of deionized water, making the molar ratio of metal chloride to NaH2PO2 1:2. Water was removed from the solution, from which the nickel and phosphate salts were fully dissolved, using an evaporator to obtain the Ni(H2PO2)2 precursor, which is a precursor of NiFeP.
[0098] The recovered Ni(H2PO2)2 precursor was spread on an alumina boat for heat treatment, placed in a furnace, and heat-treated at 300°C for 90 minutes under a 100% argon atmosphere.
[0099] After heat treatment, the mixture was washed with deionized water and filtered three times, dried in an oven at 80°C for 3 hours, and then the nickel phosphide was recovered.
[0100] Comparative Example 2: Commercially available Ir black catalyst 99.95% iridium metal powder (Ir black) prepared from Alpha Aesar was used as Comparative Example 2.
[0101] Experimental Example 1: Evaluation of the physical properties and OER activity of NiFeP catalyst based on heat treatment temperature using NaH2PO2 replacement and pyrolysis. In Experiment 1, during the preparation of nickel-iron phosphide catalyst by NaH2PO2 displacement pyrolysis in Example 2, the heat treatment temperature was changed from 300℃ to 500℃, 400℃ and 200℃ to prepare the catalyst, and experiments were conducted to evaluate the physical properties and oxygen evolution reaction (OER) activity of nickel-iron phosphide based on the heat treatment temperature.
[0102] Figure 2 This is an XRD pattern image of the catalyst prepared based on the heat treatment temperature. In the preparation method disclosed herein, the nickel-iron phosphate precursors (Ni(H2PO2)2 and Fe(H2PO2)2) contain oxygen; therefore, in response to the oxygen-bonding reaction caused by the increase in heat treatment temperature, the final product may contain impurities in the form of oxides that do not have OER activity. Therefore, from Figure 2 XRD patterns confirmed that as the heat treatment temperature increased above 400℃, the intensity of the Ni2P peak decreased, and impurities such as Fe(PO3)3, FePO4, Fe4(P2O7)3, and P2O5 were formed. At 200℃ and 300℃, only Ni2P with high OER activity was formed, with no impurity peaks. However, at 200℃, the intensity of the Ni2P peak was relatively low, approximately half that at 300℃.
[0103] Figure 3 This is a linear sweep voltammetry (LSV) plot evaluating the application of nickel-iron phosphide catalysts prepared according to heat treatment temperatures to the oxygen evolution reaction (OER) on a rotating disk electrode (RDE).
[0104] To evaluate the OER, a disk with an area of 0.247 cm² was used in the three-electrode system. 2 The RDE was used as the working electrode. An ink to be applied to the RDE was prepared, with a metal density of 700 μg / cm³. 2 The three-electrode system includes Hg / HgO as the reference electrode, Pt wire as the counter electrode, and 1M KOH as the electrolyte.
[0105] The ink of the water electrolysis anode catalyst prepared according to this disclosure using NaH2PO2 replacement and pyrolysis was applied to the RDE, dried, and then connected to a rotator. The electrode was rotated at 2500 rpm, and the LSV was measured at a scan rate of 5 mV / s in a potential range of 0.922 V to 1.92 V (vs. RHE) to evaluate the OER. Based on the measured LSV results, at 20 mA / cm 2 and 120mA / cm 2 The overpotentials at the given current densities are summarized in Table 1 below.
[0106] [Table 1]
[0107] As shown in Table 1, as the temperature rises above 400℃, the peak intensity of Ni2P, which has high OER activity, decreases, and impurities Fe(PO3)3, FePO4, Fe4(P2O7)3, and P2O5 are formed. The OER overpotential increases significantly, reaching 120 mA / cm². 2 No voltage could be detected at this point. At 200°C, the intensity of the Ni₂P peak decreased, and the overpotential was 120 mA / cm². 2 The voltage is very high, making it impossible to measure within the 1.92 V LSV scan range. XRD confirmed that Ni2P formation was optimal during heat treatment at 300 °C, resulting in the lowest measured OER overpotential and therefore the highest OER performance.
[0108] Experiment Example 2: Confirming the filling effect of NaCl Experimental Example 2 is an experiment that confirms the filling effect of sodium chloride (NaCl) contained in the precursor of this disclosure.
[0109] To verify the filling effect of NaCl alone, the NiP catalyst before and after washing during the catalyst preparation process according to Comparative Example 1 was analyzed by X-ray diffraction (XRD) patterns, surface area analysis equipment (Brunauer Emmett Teller, BET), and scanning electron microscopy (SEM) images.
[0110] Figure 4 The XRD patterns of the catalyst before and after washing during the preparation process according to Comparative Example 1 are shown. In the XRD pattern of the unwashed catalyst after heat treatment, a strong NaCl peak is clearly confirmed. In the XRD pattern of the washed catalyst, the NaCl peak completely disappears, and only the Ni₂P peak is confirmed. The results indicate that NaCl is present in the catalyst after heat treatment, but is completely removed through the washing process.
[0111] To confirm the specific surface area and pore volume before and after washing, BET was measured by adsorption and desorption of nitrogen at 77 K, and the results are summarized in Table 2 below.
[0112] [Table 2]
[0113] In the unwashed nickel phosphide catalyst, the pore volume is 0.0052 cm³. 2 / g, specific surface area is 0.56 m² 2 The surface area is very small, with almost no pores formed, resulting in a very small specific surface area for the catalyst. On the other hand, the pore volume of the nickel phosphide, the final product after washing, is 0.025 cm³.2 / g, with a specific surface area of 4.9 m². 2 / g, therefore the pores are well developed.
[0114] Figure 5 SEM images of the catalyst (a) before washing and (b) after washing during the preparation of the catalyst of Comparative Example 1 are shown. In the images at the same magnification, almost no pores are formed before washing, while pores are formed between the particles after washing. Due to the formation of a rich porous surface on the catalyst, the specific surface area of the catalyst increases, which means a larger active region where OER can occur. Furthermore, the large surface area promotes charge transfer and mass transfer, which can lead to more desirable catalytic performance.
[0115] When Figure 4 XRD patterns Figure 5 When the SEM images and the BET results in Table 2 are analyzed together, it can be seen that the NaCl filling the gaps between the nickel phosphide catalysts during the heat treatment process is completely removed during the washing process, which helps to increase the surface area.
[0116] Experimental Example 3: Confirming the effect of Fe doping in nickel-iron phosphide In Experiment 3, in order to verify the doping effect of Fe in the nickel-iron phosphide prepared in this disclosure, the following experiment was conducted: X-ray photoelectron spectroscopy (XPS) was used to measure the valence state of the nickel-iron phosphide catalyst prepared in Example 2 and the nickel phosphide catalyst prepared in Comparative Example 1 and to evaluate the OER activity.
[0117] Figure 6 The spectra of the Ni 2P and P2P regions are shown, obtained by measuring the XPS of the catalysts prepared in Example 2 and Comparative Example 1. The binding energy of 852.6 eV in the Ni 2p region is the intrinsic binding energy of nickel metal.
[0118] The binding energy of 852.65 eV measured in Comparative Example 1 is due to the binding of nickel phosphide and is offset in the positive direction compared to nickel metal, which means that nickel has lost electrons and has a partially positive charge.
[0119] Compared to Comparative Example 1, the binding energy of 853.19 eV of nickel phosphide measured in the Ni 2p region of Example 2 is shifted in a more positive direction due to the doping effect of iron.
[0120] The binding energy of 130.2 eV in the P 2P region is the intrinsic binding energy of the P element.
[0121] The binding energy of 129.1 eV measured in Comparative Example 1 and 129.3 eV measured in Example 2 is due to the binding of metal phosphides, which are offset in the negative direction compared to the P element. This means that phosphorus gains electrons from nickel and has a partially negative charge.
[0122] Figure 7 The LSV plot of OER was evaluated by applying the catalytic nickel-iron phosphide prepared in Example 2 and the catalytic nickel phosphide prepared in Comparative Example 1 to a rotating RDE.
[0123] To evaluate the OER, a disk with an area of 0.247 cm² was used in the three-electrode system. 2 The RDE was used as the working electrode. An ink to be applied to the RDE was prepared, with a metal density of 700 μg / cm³. 2 The three-electrode system includes Hg / HgO as the reference electrode, Pt wire as the counter electrode, and 1M KOH as the electrolyte.
[0124] The ink of the water electrolysis anode catalyst prepared according to this disclosure using NaH2PO2 replacement and pyrolysis was applied to the RDE, dried, and then connected to a rotator. The electrode was rotated at 2500 rpm, and the LSV was measured at a scan rate of 5 mV / s in a potential range of 0.922 V to 1.92 V (vs. RHE) to evaluate the OER. Based on the measured LSV results, at 20 mA / cm 2 and 120mA / cm 2 The overpotentials at the given current densities are summarized in Table 3 below.
[0125] Table 3
[0126] As shown in Table 3, the OER measurement results indicate that, compared with the NiP in Comparative Example 1, the NiFeP catalyst of Example 2 with added Fe exhibits a lower overpotential and significantly improved OER performance. The loss of electrons in nickel enhances its electrophilicity, leading to further adsorption of OH- ions, the reactants in alkaline water electrolysis OER, onto the electrode, thereby improving OER performance. Iron doping modifies the electronic structure of nickel phosphide, enhancing the electrophilicity of nickel and increasing the active sites for charge transfer and OH- adsorption, thus improving OER activity.
[0127] Experimental Example 4: Evaluation of the physical properties and OER activity of NiFeP catalyst with increased surface area due to NaCl recrystallization. Experiment 4 is an experiment that measures the SEM images, BET surface area, and OER performance of the NiFeP catalysts prepared in Examples 1 and 2. In Example 1, ethanol was added to the precursor solution to recrystallize NaCl, which has low solubility in ethanol, and then water was evaporated to prepare the precursor.
[0128] Figure 8 This is a schematic diagram illustrating the differences in the final products prepared according to Examples 1 and 2. In Example 1, ethanol was added to the precursor solution of Ni, Fe, and P, and NaCl was first recrystallized. After water evaporation, the resulting Ni,Fe(H2PO2)2 precursor and NaCl crystals were thoroughly mixed. After washing, porous NiFeP was prepared as the final product. In Example 2, where NaCl recrystallization with ethanol was not performed, the Ni,Fe(H2PO2)2 precursor and NaCl crystals were not thoroughly mixed but separated. Therefore, the NaCl did not fully function as a filler, and fewer pores were formed compared to Example 1.
[0129] Figure 9 SEM images of the catalysts prepared according to (a) Example 1 and (b) Example 2 are shown. At the same magnification, it is confirmed that in the case of Example 1, the addition of ethanol to pre-crystallize NaCl resulted in smaller particles and more pores.
[0130] To verify the specific surface area and pore volume of the catalysts prepared according to Examples 1 and 2, BET was measured by adsorption and desorption of nitrogen at 77 K, and the results are summarized in Table 4 below.
[0131] Table 4
[0132] The specific surface area of Example 2 is 11.9 m². 2 / g, compared to 4.9 m in Comparative Example 1 previously measured. 2 The / g ratio increased. This is because the Fe, which served as the second filler, was dissolved and removed.
[0133] In Example 1, as ethanol was added to the precursor solution, NaCl, which has low solubility in ethanol, was recrystallized, and while the solution was being evaporated, the M(H₂PO₂)₂ precursor and NaCl were effectively mixed to form uniform pores, resulting in a specific surface area of 30.9 m². 2 / g, compared to 11.9 m in Example 2 2 / g increased by about 3 times compared to the previous value.
[0134] To confirm the composition of the final products of the catalysts prepared according to Examples 1 and 2, the atomic ratios of Ni, Fe, and P measured by inductively coupled plasma optical emission spectrometry (ICP-OES) are summarized in Table 5 below.
[0135] Table 5
[0136] Nickel and phosphorus are formed in an approximately 1:1 ratio, while iron is retained in small amounts, which provides a doping effect. The iron content in Example 1 is slightly increased compared to Comparative Example 1.
[0137] Figure 10 The LSV plot of OER was evaluated by applying the catalysts prepared in Examples 1 and 2 to RDE. For OER evaluation, a disk with an area of 0.247 cm² was used in a three-electrode system. 2 The RDE was used as the working electrode. An ink to be applied to the RDE was prepared, with a metal density of 700 μg / cm³. 2 The three-electrode system includes Hg / HgO as the reference electrode, Pt wire as the counter electrode, and 1M KOH as the electrolyte.
[0138] The ink for the nickel-iron phosphide catalysts prepared in Examples 1 and 2 was applied to the RDE, dried, and then connected to a rotator. The electrode was rotated at 2500 rpm, and the LSV was measured at a scan rate of 5 mV / s over a potential range of 0.922 V to 1.92 V (vs. RHE) to evaluate the OER. Based on the measured LSV results, at 20 mA / cm 2 and 120 mA / cm 2 The overpotentials at the current densities are summarized in Table 6 below.
[0139] Table 6
[0140] from Figure 10 As can be seen from Table 6, the nickel-iron phosphide prepared in Example 1 exhibits a lower overpotential than the nickel-iron phosphide prepared in Example 2 at both low and high current densities.
[0141] Taking all factors into consideration Figure 9 and Figure 10 As shown in Tables 4, 5, and 6, in Example 1, in addition to the effect of Fe doping in the Ni2P nickel-iron phosphide of Example 2, the specific surface area increased by more than 3 times, the active area increased, the pores developed well, and mass transfer improved. Therefore, the catalytic activity increased at both low and high current densities due to the low overpotential.
[0142] This only indicates that Example 1 is superior to Example 2, and does not mean that Example 2 has no technical significance. Even when comparing the overpotential of Example 2 with that of Comparative Example 1 above and Comparative Example 2 below, it can be seen that Example 2 shows superior performance compared to the comparative examples.
[0143] Experiment Example 5: Comparison of OER performance with commercially available Ir black Experimental Example 5 is an experiment to measure the OER performance and electrical resistance of the excellent oxygen evolution reaction catalyst of Comparative Example 2, namely commercially available Ir black, and the NiFeP catalyst prepared in Example 1.
[0144] Figure 11 The LSV plot of OER was evaluated by applying the catalysts prepared in Comparative Example 2 and Example 1 to RDE. Figure 12 This is an electrochemical impedance spectroscopy (EIS) spectrum evaluated immediately after LSV measurement. For LSV and EIS measurements, a disk with an area of 0.247 cm² was used in a three-electrode system. 2 The RDE was used as the working electrode. An ink to be applied to the RDE was prepared, with a metal density of 700 μg / cm³. 2 The three-electrode system includes Hg / HgO as the reference electrode, Pt wire as the counter electrode, and 1M KOH as the electrolyte.
[0145] Commercially available Ir black from Comparative Example 2 and the ink of the nickel-iron phosphide catalyst prepared in Example 1 were applied to an RDE, dried, and then connected to a rotator. The electrode was rotated at 2500 rpm, and the LSV was measured at a scan rate of 5 mV / s over a potential range of 0.922 V to 1.92 V (vs. RHE) to evaluate the OER. Then, the EIS (vs. RHE) was measured at a potential of 1.522 V over a frequency range of 100 kHz to 100 mHz. Based on the measured LSV results, an EIS of 20 mA / cm² was used. 2 and 120mA / cm 2 The overpotentials at current densities and the ohmic resistances from the EIS plots are summarized in Table 7 below.
[0146] Table 7
[0147] like Figure 11 As shown in Table 7, the nickel-iron phosphide prepared in Example 1 exhibits a much lower overpotential than Ir black at both low and high current densities.
[0148] like Figure 12 As shown in Table 7, the nickel-iron phosphide prepared in Example 1 exhibits lower charge transfer resistance and ohmic resistance than Ir black.
[0149] Taking all factors into consideration Figure 11 and Figure 12As shown in Table 7, the nickel-iron phosphide prepared in Example 1 exhibits high OER activity due to the effect of Fe doping on Ni2P and a high specific surface area obtained due to the filler effect, thus showing a greatly improved charge transfer impedance. Furthermore, it shows a much lower overpotential than commercially available Ir black under both low and high current densities in alkaline conditions, thus demonstrating excellent OER activity.
[0150] Experimental Example 6: Demonstrating the reproducibility of using NaH2PO2 replacement and pyrolysis in the large-scale production of nickel-iron phosphate catalysts. Experimental Example 6 is an experiment demonstrating the reproducibility of the nickel-iron phosphide catalyst prepared according to this disclosure in a scale-up production process. Experiments were conducted to evaluate the OER activity of the nickel-iron phosphide prepared by varying the batch size to 0.5 g and 2 g.
[0151] Figure 13 The LSV plot of OER was evaluated by applying the catalyst prepared in Example 1 with the batch capacity changed to 0.5g and 2g to RDE.
[0152] To evaluate the OER, a disk with an area of 0.247 cm² was used in the three-electrode system. 2 The RDE was used as the working electrode. An ink to be applied to the RDE was prepared, with a metal density of 700 μg / cm³. 2 The three-electrode system includes Hg / HgO as the reference electrode, Pt wire as the counter electrode, and 1M KOH as the electrolyte.
[0153] The ink of the water electrolysis anode catalyst prepared according to this disclosure using NaH2PO2 replacement and pyrolysis was applied to an RDE, dried, and then connected to a rotator. The electrode was rotated at 2500 rpm, and the LSV was measured at a scan rate of 5 mV / s in a potential range of 0.922 V to 1.92 V (vs. RHE) to evaluate the OER. Even with capacity changes, the OER overpotential of the final product NiFeP did not change. Therefore, all OER properties of the product produced on a scale-up basis can be reproduced as is.
[0154] Therefore, the method for preparing the nickel-iron phosphate catalyst disclosed herein is to prepare nickel-iron phosphate by pyrolyzing the nickel-iron hypophosphite precursor formed in NaH2PO2 with nickel and iron instead of sodium. The contact with the gas supplied to the furnace is not important, so large-scale production can be carried out according to the increase of the capacity of the precursor to be heat-treated.
Claims
1. A method for preparing a nickel-based phosphide represented by the following chemical formula 1, comprising the following steps: Nickel chloride (as the first metal), chloride of the second metal (M), and sodium hypophosphite (NaH2PO2) are dissolved in water (step 1); Evaporate the solvent to obtain a mixture of nickel phosphide precursor and second metal phosphide precursor (step 2); The nickel phosphide precursor and the mixture of the second metal phosphide precursor are pyrolyzed to obtain a composition containing nickel-based phosphides (step 3); and Wash the composition with water to obtain a nickel-based phosphide (step 4): [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
2. The method for preparing nickel-based phosphides according to claim 1, wherein: After step 1, The method further includes adding a solvent to a solution of nickel chloride, second metal (M) chloride and sodium hypophosphite dissolved in water to recrystallize sodium chloride (NaCl).
3. The method for preparing nickel-based phosphides according to claim 1, wherein: The nickel phosphide precursor is nickel hypophosphite, and the second metal phosphide precursor is second metal hypophosphite.
4. The method for preparing nickel-based phosphide according to claim 1, wherein: In step 1, 200 to 300 moles of sodium hypophosphite are mixed relative to 100 moles of nickel chloride and the second metal chloride.
5. The method for preparing nickel-based phosphides according to claim 1, wherein: The second metal (M) is Fe.
6. The method for preparing nickel-based phosphides according to claim 1, wherein: In step 1, The mixing ratio of nickel chloride and the second metal chloride is 30 to 300 moles of the second metal chloride for every 100 moles of nickel chloride.
7. The method for preparing nickel-based phosphides according to claim 1, wherein: In step 4, The pyrolysis temperature is 250℃ to 500℃.
8. The method for preparing nickel-based phosphides according to claim 2, wherein: The solvent is ethanol.
9. The method for preparing nickel-based phosphides according to claim 1, wherein: In step 5, pyrolysis byproducts and second metals are removed from the composition containing nickel-based phosphides.
10. The method for preparing nickel-based phosphides according to claim 1, wherein: The water used in steps 1 to 2 or 4 is deionized water.
11. A nickel-based phosphide, said nickel-based phosphide being represented by the following chemical formula 1, and having a concentration of 10m. 2 / g or larger BET surface area: [Chemical Formula 1] NiM x P y Where x ranges from 0.01 to 0.15, y ranges from 0.5 to 1.2, and M is selected from one or more of the group consisting of Fe, Mo, Co, Mn, Cu, Zn, Cr and V.
12. An alkaline water electrolysis system comprising the nickel-based phosphide according to claim 11 as an anode catalyst.
Citation Information
Patent Citations
Method and system for infrared detection
KR1020230104171A